Analisis Wacana Van Dijk Pada Berita Kekerasan Jurnalis Media Online Kompas.com - Mulyani, Ani; Suryana, Cecep; Darsiyah, Enok (Annaba: Jurnal Ilmu Jurnalistik, 2020)
Journalists experienced violence during a demonstration against the Job Creation Law in October 2020. Kompas.com is an online media site that often reports on cases of violence, including violence experienced by journalists while covering demonstrations. The aim of this research is to examine news texts regarding violence experienced by journalists while covering demonstrations. This study uses a qualitative methodology, using Teun A. Van Dijk's critical discourse analysis. The results of this research are; Macro Structure (Thematic), highlighting many of the themes of responses from figures who condemn violence against journalists. Superstructure (Schematic), the news is completely arranged and meets the main elements of writing. Microstructure (Semantics), many meanings in the news. (Syntax), balanced inductive and deductive sentences. (Stylistics), some texts use a choice of vocabulary and adjectives. (Rhetorical), using lots of emphasis, such as bold letters, metaphors and photos in the news. The violence experienced by journalists is something that no one can condone, because it violates human rights, freedom of expression and harms Indonesian democracy.